1998
DOI: 10.1007/s005860050107
|View full text |Cite
|
Sign up to set email alerts
|

Sacroiliac joint dysfunction in patients with imaging-proven lumbar disc herniation

Abstract: IntroductionDisc herniation leading to nerve root displacement with compression and causing radicular symptoms is only one of a variety of possible causes of lumbar and ischiadic pain. Pain radiating into the leg is not necessarily caused by irritation of the root [18,19]; Norman and May [25] identified the sacroiliac joint (SIJ) as one of the possible starting points of such complaints via injection of local anaesthetic. Disc herniations were detected on CT and MR scans in a high percentage of asymptomatic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Also, by using Wilcoxon signed-rank test, we observed significant improvements in VAS and ODI within two groups throughout the trial. The positive finding in our study is in accord with findings of previous studies (Osterbauer et al, 1993;Galm et al, 1998;Shearar et al, 2005;Cleland et al, 2009), although, to the author's knowledge, there is no similar study comparing two manual manipulative therapy techniques for patients with SIJ syndrome; this correlate with our study. Also, significant differences in ODQ score were obtained in favor of the thrust manipulation group as compared to mobilization group.…”
Section: Comparison Of Outcomessupporting
confidence: 96%
See 1 more Smart Citation
“…Also, by using Wilcoxon signed-rank test, we observed significant improvements in VAS and ODI within two groups throughout the trial. The positive finding in our study is in accord with findings of previous studies (Osterbauer et al, 1993;Galm et al, 1998;Shearar et al, 2005;Cleland et al, 2009), although, to the author's knowledge, there is no similar study comparing two manual manipulative therapy techniques for patients with SIJ syndrome; this correlate with our study. Also, significant differences in ODQ score were obtained in favor of the thrust manipulation group as compared to mobilization group.…”
Section: Comparison Of Outcomessupporting
confidence: 96%
“…Osterbauer et al (1993) applied mechanical forced manipulation (in contrast with our study that compare two manual manipulative therapy techniques) in patients with SIJ syndrome, and a decrease in pain, disability and pain pressure threshold was obtained after one year of follow up. Galm et al, (1998) reported a significant improvement after manual therapy treatment on SIJ in patients with imaging proven lumbar disc herniation that had SIJ dysfunction. If dysfunctions of the SIJ were present the patients were treated by manual therapy accordingly.…”
Section: Comparison Of Outcomesmentioning
confidence: 96%
“…However, the different pathophysiologies of low-back pain do not occur in isolation, and more than one pathophysiology commonly occurs in any individual patient. 24,25 All patients in the present study carried radiographic evidence of some other degenerative process. The 2 groups differed with respect to the concomitant presence of facet arthropathy (greater in patients with SI syndrome) and spondylosis (greater in patients with lumbar radiculopathy).…”
Section: Discussionmentioning
confidence: 70%
“…We therefore advocate to perform at least an MRI of the spine before a definitive diagnosis of SIJ-related leg pain is made. Moreover, as described by Galm et al [10] SIJ dysfunction can occur in patients with low back pain and sciatica and imaging-proven disk herniation. When therapy is focused on the presence of SIJ dysfunction nucleotomy can be prevented in these patients [10].…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, as described by Galm et al [10] SIJ dysfunction can occur in patients with low back pain and sciatica and imaging-proven disk herniation. When therapy is focused on the presence of SIJ dysfunction nucleotomy can be prevented in these patients [10]. Can factors from the medical history or clinical examination be used to differentiate between SIJ-related pain, leg pain due to disk herniation or a combination of both?…”
Section: Discussionmentioning
confidence: 84%